The right to repair : reclaiming control over the things we own - Perzanowski, Aaron (Cambridge : Cambridge University Press, 2022)
In recent decades, companies around the world have deployed an arsenal of tools - including IP law, hardware design, software restrictions, pricing strategies, and marketing messages - to prevent consumers from fixing the things they own. While this strategy has enriched companies almost beyond measure, it has taken billions of dollars out of the pockets of consumers and imposed massive environmental costs on the planet. In The Right to Repair, Aaron Perzanowski analyzes the history of repair to show how we've arrived at this moment, when a battle over repair is being waged - largely unnoticed - in courtrooms, legislatures, and administrative agencies. With deft, lucid prose, Perzanowski explains the opaque and complex legal landscape that surrounds the right to repair and shows readers how to fight back.
Introduction -- Why repair matters -- The history of repair -- Breaking repair -- Repair & intellectual property -- Repair & competition -- Repair & consumer protection -- Rebuilding repair.
Title from publisher's bibliographic system (viewed on 30 Dec 2021).
Keywords: Consumer goods -- Maintenance and repair -- Law and legislation -- United States; Consumer goods -- Maintenance and repair -- Law and legislation